A critical review of the impact of IT on organisational flexibility - Hui, Liu (Auckland University of Technology, 2013)
Increasing unpredictability and competition as markets globalize means that it is important for organisations to be able to respond to change effectively. While researchers have argued that IT use can lead to a more flexible organizational structure, others have found that this is not necessarily so. A challenge in this field is the ambiguity of the key concepts and a lack of integration into a nomological network. For example, there are many different types of information technology resources, and organisational flexibility is a multidimensional concept (e.g. organisations may have operational, structural and strategic flexibilities) (Golden & Powell, 2000; Volberda, 1996). Thus, studying only one type of IT resource or one aspect of organisational flexibility could mean neglecting the others. This study reviews the literature to understand the relationship between IT and organisational flexibility. Eighty-three relevant articles were located after an extensive search. 95% of them concluded that different types of IT resources could directly or indirectly contribute to some aspect of organisational flexibility. Moreover, different types of IT resources contributed to different types of organisational flexibilities. The study summarises the findings of the review and provides directions for future research in this area.
Keywords: Impact of IT; Organisational flexibility